1995
DOI: 10.1074/jbc.270.37.21779
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a cis-Regulatory Element for Δ12-Prostaglandin J2-induced Expression of the Rat Heme Oxygenase Gene

Abstract: We recently reported that delta 12-prostaglandin (PG) J2 caused various cells to synthesize heme oxygenase, HO-1 (Koizumi, T., Negishi, M., and Ichikawa, A. (1992) Prostaglandins 43, 121-131). Here we examined the molecular mechanism underlying the delta 12-PGJ2-induced HO-1 synthesis. delta 12-PGJ2 markedly stimulated the promoter activity of the 5'-flanking region of the rat HO-1 gene from -810 to +101 in rat basophilic leukemia cells. From functional analysis of various deletion mutant genes we found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
2

Year Published

1995
1995
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 36 publications
0
23
2
Order By: Relevance
“…Clearly, the exact mechanism of action of 15d-PGJ 2 in microglia remains undefined. One possible clue is the induction of heme oxygenase-1, BiP, and hsp70 by 15d-PGJ 2 as observed in other cell types (29,33,34). However, the doses of 15d-PGJ 2 used in those studies were about 10-fold higher than in this study, and it remains to be seen whether these effects are relevant to the inhibition of iNOS in microglia.…”
Section: Discussioncontrasting
confidence: 49%
“…Clearly, the exact mechanism of action of 15d-PGJ 2 in microglia remains undefined. One possible clue is the induction of heme oxygenase-1, BiP, and hsp70 by 15d-PGJ 2 as observed in other cell types (29,33,34). However, the doses of 15d-PGJ 2 used in those studies were about 10-fold higher than in this study, and it remains to be seen whether these effects are relevant to the inhibition of iNOS in microglia.…”
Section: Discussioncontrasting
confidence: 49%
“…In this context, 15dPGJ 2 has been shown to inhibit the expression of inducible NO synthase, as well as tumor necrosis factor-␣ and interleukin-1␤ production in mouse and human macrophages, thus suggesting a role for 15dPGJ 2 in the inhibition of inflammation (16,17). Available data also suggest that the induction of heme oxygenase-1 (HO-1) expression elicited by ⌬ 12 -PGJ 2 in rat basophilic leukemia cells and other cell types involved in the inflammatory response may play an important role in the fate of heme liberated during inflammation, and thus an anti-inflammatory role has been ascribed to ⌬ 12 -PGJ 2 (18). In this view, 15dPGJ 2 has been suggested to play a feedback regulatory role in the resolution phase of inflammation and hence is considered as a potential therapeutic target for the treatment of inflammatory diseases (1).…”
Section: -Deoxy-⌬mentioning
confidence: 99%
“…Recent studies have illustrated that 15dPGJ 2 induces HO-1 expression in a variety of cells, including hepatocytes (31), cardiac myocytes (32), microglial cells (33), murine macrophages (34), and rat basophilic leukemia cells (18). Also, it has been shown that 15dPGJ 2 is able to induce apoptosis in mouse T cells and to inhibit T cell activation (7,8,35).…”
Section: -Deoxy-⌬mentioning
confidence: 99%
“…In RBL-2H3 cells, 12-O-tetradecanoylphorbol-13-acetate could not induce the HO-1 gene expression (data not shown). We recently demonstrated that the A'Z-PGJ2-induced HO-1 gene expression was mediated by the binding of nuclear proteins, the A'Z-PGJ2 -responsive factors, to the A12-pGJ2-responsive c/s-regulatory element [15]. Thus, we examined the effects of these inhibitors on the A]2-pGJ2-stimulated nuclear protein binding to the element.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we identified the A~Z-PGJ2-specific cis-regulatory element, the AL2-pGJ2-responsive element, located in the 5'-flanking region of HO-I gene, for AtZ-PGJ zinduced expression of the HO-1 gene, and two specific nuclear factors, the Al2-pGJ2-responsive factors, which bind to the element in response to A~2-PGJ2 [15], However, the molecular mechanisms for the AlZ-pGJz-induced nuclear factor binding to the element remain unclear. The DNA binding activity of nuclear transcription factors has been shown to be modulated by phosphorylation [16].…”
Section: Introductionmentioning
confidence: 99%